2009
DOI: 10.2478/s11756-009-0170-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of stj fimbrial operon in the intestinal persistence of Salmonella Typhimurium in mice

Abstract: Salmonella Typhimurium contains 13 operons coding for fimbriae with unique binding specificities to host epithelial surfaces. stj operon is only detected in S. Typhimurium genome suggesting that Stj fimbria may effect serovarspecific virulence characteristics. In this study, the role of stj fimbrial operon in the long-term persistence of S. Typhimurium was identified by competitive infection experiment in genetically resistant mouse (CBA) model system. Knock-out mutation of stjA (major subunit of the Stj fimbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Typhimurium MA2 mutant, with stjE::LacZYA fusion, generated by Akkoç et al (1) was used in activation of stj fimbrial operon via transposon (T-POP) mutagenesis. Expression of stj fimbrial operon by phenotypic characterisation after transduction of T-POP transposon to S. Typhimurium MA2 mutant shows that it harboured the transposase gene.…”
Section: Smentioning
confidence: 99%
See 3 more Smart Citations
“…Typhimurium MA2 mutant, with stjE::LacZYA fusion, generated by Akkoç et al (1) was used in activation of stj fimbrial operon via transposon (T-POP) mutagenesis. Expression of stj fimbrial operon by phenotypic characterisation after transduction of T-POP transposon to S. Typhimurium MA2 mutant shows that it harboured the transposase gene.…”
Section: Smentioning
confidence: 99%
“…Until recently, there has been no information on the role of Stj fimbriae in virulence or persistence of S. Typhimurium in the host systems. Akkoc et al (1) showed that stj fimbrial operon affected colonization and persistence of S. Typhimurium in mouse model systems. Protein sysnthesis patterns obtained from this study also confirmed that Stj fimbriae in S. Typhimurium was expressed in bacteria during infection in the host.…”
Section: Smentioning
confidence: 99%
See 2 more Smart Citations